Prevalence and factors associated with memory disturbance and dementia after acute ischemic stroke - Jesada Surawan; Teabpaluck Sirithanawutichai; Suchat Areemit; Somsak Tiamkao; Suprawita Saensak (MDPI AG, 2018)
Prevalence and risk factors associated with memory disturbance and dementia were determined in acute ischemic stroke (AIS) patients in hospitals before discharge, three and six months after stroke. A prospective cohort study was conducted during January-December 2017 with 401 AIS patients admitted to Srinagarind Hospital, Khon Kaen Hospital and Chum Phae Hospital, Khon Kaen, Thailand. The demographics and clinical characteristics, previous illness and past medical history, and laboratory test results of the patients were collected from the medical records, while depression screening, NIH stroke scale (NIHSS) scoring and mini mental state examination (MMSE) were performed using particular medical record forms. The prevalence of memory disturbance and dementia was 56.6, 41.6 and 38.2% before discharge, three and six months after stroke, respectively. Based on logistic regression analysis, age, education and stroke severity were the risk factors associated with the studied disorders before discharge and three months after stroke. Meanwhile, age and education were the risk factors for six months after stroke. Our findings suggested that the prevalence of memory disturbance and dementia remained high at all study periods.